Comparison of SWAT and GeoWEPP model in predicting the impact of stone bunds on runoff and erosion processes in the Northern Ethiopian Highlands. - Melaku, Nigus D.; Flagler, J.; Renschler, Chris; Zucca, Claudio; Ziadat, Feras M.; Strohmeier, Stefan; Addis, H.K.; Bayu, Wondimu; Klik, Andreas; Holzmann, H. (2017)
In the Ethiopian Highlands deforestation increased the vulnerability of the soils due to rainfall driven soil erosion (Addis et at. 2016; Nyssen et al. 2000). To tackle this soil erosion problem soil and water conservation strategies are considered were constructed. Two neighboring subwatersheds, Abakaloye and Ayaye, were selected to investigate the impact of soil and water conservation structures on soil erosion processes. Soil and water conservation structures were applied in the Ayaye subwatershed while Abakaloye subwatershed was used as a reference without soil and water conservation structures. Soil and Water Assessment Tool (SWAT) (Arnold et al., 1998) and GeoWEPP (Renschler, 2003) models were used.